ANTHRAX in INDONESIA - Rahayu, Asih (Universitas Wijaya Kusuma Surabaya, 2009)
Anthrax is a zoonosis disease caused by Bacillus anthracis bacteria. This bacteria is able to produce an endospora that lasts for decades inside the soil and thus becomes an infection source (endemic areas), causing difficulties to eradicate this disease in Indonesia. This disease mainly infects cattle such as cows, goats, horses, and pigs in some cases. It can also infect humans through three ways which is per cutaneous, per oral, and per inhalation. The clinical manifestations in humans are malignant pustule, hematemesis, pneumonia hemorrhagic or meningitis. The success of eradicating anthrax from humans fully depends on the eradication of this disease from the animals.